MENINGKATKAN PRESTASI BELAJAR SISWA DALAM PENDIDIKAN AGAMA KATOLIK DENGAN PENDEKATAN STUDENT TEAM ACHIEVEMENT DIVISION PADA KELAS VII DI SPMN SATU ATAP TIKATUKANG - Magareta Ayuningsih Nerok Ola; Maria Magdalena Wola (CV. ADIBA AISHA AMIRA, 2025)
This study aims to improve students' learning achievement in Catholic Religious Education subjects through the STAD approach. The STAD approach is one of the cooperative learning models that emphasizes group and individual cooperation to achieve common learning goals. This study was conducted at SMPN Satu Atap Tikatukang in class VII with 17 students who were divided into small groups. The method used was classroom action research with a cycle consisting of planning, action, observation and reflection. The results of the study showed an increase in learning achievement after the implementation of the STAD approach, both in terms of exam scores, active participation in group discussions, and understanding of the material taught. Based on these results, it can be concluded that the STAD approach is effective in improving students' learning achievement in Catholic religious education.